Cigarettes: Between Behavior, Habits, and Law - Siregar, Pani Akhiruddin; Suryani, Suryani; Saragih, Nilam Permata (Sharia and Law Faculty, 2023)
Tobacco products known as cigarettes are strongly opposed because of the large amount of toxins contained in them. Although the government has given warnings about the dangers of smoking. However, it did not have an effect. This research aims to examine Cigarettes: Between Behavior, Habits, and Law. Qualitative research methods with a normative legal approach. Research results: (1) Smoking habit. Smoking is currently a frequent behavior. In fact, the realization of the preservation of the soul in Islam is the most important part. For, the preservation of the soul simultaneously sees the need for the preservation of the body by not getting used to smoking; (2) Smoking consumption and smoking behavior. The consumer behavior of smokers has taken its decision to continue consuming cigarettes. In the future, consumer smokers constantly needed cigarettes as a smoking need; and (3) Smoking laws according to Islamic organizations in Indonesia: (1) Smoking mubah according to Nahdhatul Ulama (NU) and the Islamic Union (PERSIS); (2) Smoking is makruh and haram according to the Indonesian Ulema Council (MUI); and (3) Smoking is haram according to Muhammadiyah.